Peluang dan Tantangan Bisnis Kriya saat Pandemi Covid-19 - Santi Susanti (Jurnal Pengabdian Pada Masyarakat, 2021)
OPPORTUNITIES AND CHALLENGES OF CRAFT BUSINESS DURING THE COVID-19 PANDEMIC. The creative economy is one sector affected by the Covid-19 pandemic. Production and distribution of products remained disrupted, because of cancellations or delays in delivery of orders. The purchasing power of the people has also decreased so that sales of MSME products have decreased, and producers have lowered the selling price of the products. To survive during a pandemic, creative economy players apply strategies in the production and marketing of their products. On this basis, this Community Service activity held under the title “Opportunities and Challenges of Craft Business During the Covid-19 Pandemic”. This activity aims to increase the understanding and awareness of PPM participants regarding the challenges and opportunities in doing craft business during the Covid-19 pandemic. The PPM held on Friday, 29 January 2021, at 1 PM-finished, through the Zoom Meetings application and presenting speakers Anthony Sutrisno (jewelry designer and owner of Bumi Putih Spiritual Jewelry), Ani Wari’ah, and Iwan Ramdani, owners of Rineka Karya Art, and Rachmaniar, Lecturer in Communication Studies Program, Faculty of Communication Sciences, University of Padjadjaran. The PPM results show that to survive the Covid-19 pandemic, a creative economy artist must innovate the products they produce, and strengthen product quality so that buyers will remember them. Also, they can take advantage of social media in marketing their products so that they are widely recognized by the public. The conclusion of this PPM creativity to produce works that have a strong and innovative character is a strong asset for artists and artisans to maintain their business during the Covid-19 pandemic.